Threshold voltage control of 2,3 benzanthracene organic thin-film transistor by visible light for integration of transistors into electronic circuits - Yakuphanoğlu, Fahrettin; Farooq, W. Aslam (Elsevier Science Sa, 2011)
The organic field-effect transistor having 2,3 benzanthracene as active layer grown on SiO2 dielectric layer was fabricated. AFM results indicate that 2,3 benzanthracene thin film is formed from homogeneous small crystal grains with an average diameter about 200 nm. The electrical parameters such as mobility, threshold voltage, I-on/I-off ratio and SS value were determined. The obtained I-on/I-off and S values increase with visible light illumination due to more photogenerated charges. The mobility and threshold values were changed by visible light illumination. The organic thin film transistor exhibits a photovoltaic effect in turn-on state. The control of the threshold voltage of 2,3 benzanthracene-based organic thin film transistor was achieved by visible light illumination. The change in the threshold voltage is enough for the electronic technology applications of organic thin film transistors. (C) 2010 Elsevier B.V. All rights reserved.
Keywords: Organic thin film transistor; 2,3 Benzanthracene; Photovoltaic effect